Seasonal Fluctuations of Pigments and Biomass of Phytoplankton in Lentic Water Bodies of Bhadravathi Taluk, Karnataka, India - Ajayan K. V.; Parameswara Naik T. (Emerging Issues in Environment, Geography and Earth Science Vol. 8, 2024)
The present investigation revealed that biomass of phytoplankton by chlorophyll estimation method shows that Chl.a, Chl.b and Chl.c distributions were unequal. The pigment diversity and quantity of phytoplankton in lentic water bodies are critical to the general health and function of aquatic ecosystems. Quantification of phytoplankton biomass and community composition is important for understanding the structure and dynamics of fresh water ecosystems. The minimum concentration of Chl.a was 0.112mg/L during November at BVTS3 and maximum .077 mg/L was recorded same station in the month of December. The Chl.b concentration was 0.0023mg/L minimum during October at BVTS1 and maximum 0.6118mg/L during August at BVTS3 and 0.0083 mg/L Chl.c was minimum during October at BVTS3 and maximum 3.894 in October at BVTS4.The correlation coefficient of six physico-chemical parameters show fluctuating the positive and negative correlation with different chlorophyll pigments. The Chl.c shows positive correlation with magnesium but others not. In BVTS1 of Chl.a, b and c show positive correlation with water temperature, pH bicarbonate and other stations were not showed the positive correlation. A wide variety of pigments are present in phytoplankton, which helps them to absorb light energy for photosynthesis. Effective management, conservation, and resolution of environmental issues depend on an understanding of the pigment diversity and biomass of phytoplankton in lentic water bodies. The study help determine the variables impacting phytoplankton growth, comprehend the health of ecosystems, and develop efficient management plans for the preservation and sustainable use of aquatic resources.